2004
DOI: 10.1002/elps.200405971
|View full text |Cite
|
Sign up to set email alerts
|

Enantioseparation using sulfated cyclosophoraoses as a novel chiral additive in capillary electrophoresis

Abstract: Highly sulfated cyclosophoraoses (HS-Cys) were synthesized by the chemical modification of a family of neutral cyclosophoraoses isolated from Rhizobium leguminosarum bv. trifolii. The HS-Cys were then analytically characterized using Fourier transform-infrared spectroscopy and elemental analysis. These HS-Cys were successfully used as a novel chiral additive, in low-pH aqueous background electrolytes, for capillary electrophoretic separation of five basic chiral drugs such as arterenol, atenolol, isoproterenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Electrostatic interactions provide additional stereoselectivity effects in case of ionic polysacharides [131] (heparin, dextran sulfate, chondroitin sulfate, hyaluronate, chitosans, aminoglycosides, colominic acid, highly sulfated cyclosophoraoses) suitable for a variety of basic drugs such as b-blockers and sympathomimetics [131][132][133][134].…”
Section: Polysaccharidesmentioning
confidence: 99%
“…Electrostatic interactions provide additional stereoselectivity effects in case of ionic polysacharides [131] (heparin, dextran sulfate, chondroitin sulfate, hyaluronate, chitosans, aminoglycosides, colominic acid, highly sulfated cyclosophoraoses) suitable for a variety of basic drugs such as b-blockers and sympathomimetics [131][132][133][134].…”
Section: Polysaccharidesmentioning
confidence: 99%
“…For the anionic contribution, carboxymethylation was carried out using monochloroacetic acid in alkaline conditions, and the cyclic b-(1,2) glucans were substituted with carboxymethyl groups at C4 and 6 positions of glucose with DS ranging from 0.012 to 0.290 [95][96][97]. Sulfated cyclic b-(1,2) glucans were synthesized from a reaction of cyclic b-(1,2) glucans and sulfur trioxide trimethylamine complex in dimethylformamide at 60-70°C for 24 h [98]. The average sulfate contents were 2.25 per glucose.…”
Section: Natural and Chemical Derivatizationmentioning
confidence: 99%
“…Additional studies have indicated that sinorhizobial cyclic β-(1,2)-glucans have the potential for use as commercial complexation agents for a variety of poorly soluble molecules (54)(55)(56)(57)(58)(59). Recent studies have also shown that cyclic β-(1,2)-glucans act as chiral selectors for various enantiomers (60)(61)(62)(63)(64)(65)(66), as catalytic carbohydrates for methanolysis (67)(68)(69), and as morphology-directing agents for the synthesis of selenium nanowires (70). These characteristic functions of PGs may be due to inherent three-dimensional structures, hydrogen-bonding and the complex-forming abilities of the cyclic glucans in aqueous solutions.…”
Section: Novel Physico-chemical Properties Of Pgsmentioning
confidence: 99%